A study of systemic risk spillovers in Asian emerging markets and Chinese stock market - Zhongzheng Fang (PLoS ONE, 2025)
This study examines systemic risk spillover effects between China’s Shanghai Stock Exchange (SSE) and seven Asian emerging markets within the context of increasing global financial integration. Utilizing Quantile Regression and Conditional Value-at-Risk (CoVaR) methodologies, this study provides a new perspective on understanding the asymmetry of systemic risk transmission between China and Asian emerging markets. Based on data from 2000 to 2024, the findings reveal significant spillover patterns, with Korea (KOSPI) showing high sensitivity to SSE risks, Malaysia (KLCI) exerting strong influence, and Thailand (SET) and Taiwan (TWII) emerging as key contributors and receivers of systemic risk. Under extreme market conditions, risk spillovers intensify, positioning SSE as a central hub in regional risk dynamics. These insights underscore the need for robust macroprudential policies and enhanced regional cooperation to mitigate systemic vulnerabilities, contributing to both the theoretical discourse on financial risk and its practical management.